Seicho no ie: idosos migrantes de religiões - Rodrigues, Thuam Silva (2015)
The relation between aging and religion is currently being more widespread in the scientific and academic literature, the religion would be, to the human been, a parameter of conducts organization, and interpretation of experience in different situations of confrotation to life conditions, in any culture and in many age groups, which fact would help positively experience the aging and old age process. The demographics data show dynamic displacement of people among the various religious groups in the country, for example Seicho no le, which has been protuding specially for being constituted by brazilian non-oriental more than Japonese immigrant descendents. However, this religion change only will happen fully if held in symbolic. The symbolic transits to the alterity, difference and metaphor and produces a new sense. Lastly, the religions are constituted as symbolic capital sources, giving sense to the new experiences. The research methodologhy, to undestand the reality of the narratives of the individuals was applied the tools of qualitative and quantitative research (semi-structured questionnaire), with the elders, using the technique of the recorder. Was selected 15 people, the inclusion of this individuals was according to the following criteria: sixty years or aged superior, of both sexes, who migrated from one religion to the Seicho no Ie, and participate there more than a year. The quantitative data analysis was obtained through the data treatment by software Statiscal Packet Social Science SPSS 11.0 for Windows. The qualitative data was analysed, following two phase: analisys of data to identify the categories that enhance and then perform the descriptive interpretation based on the analysis of the literature results. The results analisys showed that the main factor of migration of elders to Seicho no Ie was through the sense of healing and solutions to family problems, an original way and with its own fascination of symbolic universe able to convince people on the treatment of the disease. Although the elders claim perform the Seicho no Ie rituals, they keep the catolicism as symbolic core, everyone state perform prayers and catolicism rituals. In other words, there is not a conversion of a catholic person to Seicho no le but a religious duplicity, in which there is a new interpretation or symbolic system increase, enabling acceptance to the symbolic of Seicho no Ie, we can observe the intense dedication to Seicho no Ie rituals, and low frequency to Catholic rituals. About the meaning of Seicho no Ie, for the elderly, the vast majority defines the Seicho no Ie as a religion and filosifia that teaches them how to live better